Wettability Patternable Hybrid Polymer Films Based on TiO2 and Fluorinated Polymer for Bioelectronics Applications - Shunsuke Yamamoto; Hiroyuki Kai (Advanced Materials Interfaces)
Abstract Organic–inorganic hybrid films based on TiO2 and a fluorinated polymer are fabricated, and their properties are investigated for bioelectronic applications. The analysis revealed that the preparation process requires (1) aging the blend solution before spin coating and (2) spin coating under humid conditions to obtain hydrophobic honeycomb‐like surfaces. Ultraviolet (UV) irradiation changed the surface wettability to hydrophilic, and patterned irradiation resulted in hydrophobic‐hydrophilic surface patterns. Patterned hybrid films have been used as substrates in both open microfluidics and organic electrochemical transistor applications. This multimodal application will open up an integrated biosensing device that collects body fluids and analyzes them on a single platform.